Acute and subacute oral toxicity of copper oxide nanoparticles in female albino Wistar rats. Issue 5 (7th January 2019) - Bugata, Lakshmi Sai Pratyusha; Pitta Venkata, Prabhakar; Gundu, Ananth Reddy; Mohammed Fazlur, Rahman; Reddy, Utkarsh A.; Kumar, Jerald Mahesh; Mekala, Venugopala Reddy; Bojja, Sreedhar; Mahboob, Mohammed
Abstract: The extensive use of copper oxide nanoparticles (CuO‐NPs) in various industries and their wide range of applications have led to their accumulation in different ecological niches of the environment. This excess exposure raises the concern about its potential toxic effects on various organisms including humans. However, the hazardous potential of CuO‐NPs in the literature is elusive, and it is essential to study its toxicity in different biological models. Hence, we have conducted single acute dose (2000 mg/kg) and multiple dose subacute (30, 300 and 1000 mg/kg daily for 28 days) oral toxicity studies of CuO‐NPs in female albino Wistar rats following OECD guidelines 420 and 407 respectively. Blood analysis, tissue aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase and acetylcholinesterase, superoxide dismutase, catalase, lipid malondialdehyde and reduced glutathione assays, and histopathology of the tissues were carried out. The higher dose treatments of the acute and subacute study caused significant alterations in biochemical and antioxidant parameters of the liver, kidney and brain tissues of the rat. In addition, histopathological evaluation of these three organs of treated rats showed significantly high abnormalities in their histoarchitecture when compared to control rats. We infer from the results that the toxicity observed in the liver, kidney and brain of treated rats could be due to the increased generation of reactive oxygen species by CuO‐NPs. Abstract : We conducted single and repeated oral dose toxicity studies of copper oxide nanoparticles in female albino Wistar rats. Results revealed significant alterations in biochemical, blood and histopathological parameters of the liver, kidney and brain tissues at higher dose treatment in acute and subacute studies indicating an oxidative stress condition.